2012
DOI: 10.1371/journal.pone.0033597
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-Kappa B Inhibition Can Enhance Apoptosis of Differentiated Thyroid Cancer Cells Induced by 131I

Abstract: ObjectiveTo evaluate changes of nuclear factor-kappa B (NF-κB) during radioiodine 131 (131I) therapy and whether NF-κB inhibition could enhance 131I-induced apoptosis in differentiated thyroid cancer (DTC) cells in a synergistic manner.MethodsThree human DTC cell lines were used. NF-κB inhibition was achieved by using a NF-κB inhibitor (Bay 11-7082) or by p65 siRNA transfection. Methyl-thiazolyl-tetrazolium assay was performed for cell viability assessment. DNA-binding assay, luciferase reporter assay, and Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
7
28
1
Order By: Relevance
“…Our recent in vitro experiment revealed that 131 I could induce NF-κB activation, which attenuated 131 I induced apoptosis. NF-κB inhibition was effective in suppressing NF-κB regulated anti-apoptotic changes and in combined regimen apoptosis was achieved synergistically (Meng et al, 2012). This work also showed the NF-κB inhibition approach did not significantly influence iodine uptake of DTC cells.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our recent in vitro experiment revealed that 131 I could induce NF-κB activation, which attenuated 131 I induced apoptosis. NF-κB inhibition was effective in suppressing NF-κB regulated anti-apoptotic changes and in combined regimen apoptosis was achieved synergistically (Meng et al, 2012). This work also showed the NF-κB inhibition approach did not significantly influence iodine uptake of DTC cells.…”
Section: Introductionmentioning
confidence: 62%
“…The multi-well colorimetric assay for active NF-κB function was performed (Meng et al, 2008(Meng et al, , 2012Starenki et al, 2004a,b). Briefly, equal amounts of nuclear extracts were incubated in 96-well plates coated with immobilized oligonucleotide containing a NF-κB consensus binding site.…”
Section: Dna-binding Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…BAY 11‐7082 was selected as a reliable inhibitor of NF‐κB pathway that has been widely used in many studies exploring the effect of NF‐κB 11, 24, 25. It has been suggested that BAY 11‐7082 offers the most rapid and potent antitumour effect among other NF‐κB inhibitors 24 and can possibly be used as a sensitizer of anticancer therapy,26, 27 increasing the intrinsic susceptibility of cancer cells to chemotherapeutic agents 28…”
Section: Introductionmentioning
confidence: 99%